ELLIPSE - BASED TEMPLATE MATCHING FOR CELL IDENTIFICATION IN FLUORESCENCE MICROSCOPE IMAGES - MKAYES, ABED ALRAHMAN (2016)
Automatic Cell detection in fluorescence microscopy(FM)images is essential operation in automated cell analysis for diagnosis and treatment of oral cancer which includes the study of cell shapes.The biologists are able to detect, count all the cells automatically in FM images which provide high reliability and fasten the clinicians work. In this work, a cell detection method in FM images obtained from Cancer Research Malaysia is proposed. This method is divided into two main stages, cell enhancement, and cell detection. The aim of cell enhancement is to remove unwanted noise and enhance cells boundary prior to cell detection operation. This work presents a non-exhaustive comparison between several linear and non-linear filters applied to FM images. The performance of the enhancement techniques is evaluated and tested in terms of PSNR and ASNRon 30 FM images that exhibiting low contrast and non-uniform illumination. Results from this experiment indicate that non-linear filters give better contrast and background removal than the linear filters.